Improving farming practices in flood-prone areas in the Solomon Islands - Sese, Elmah Panisi (Technical Centre for Agricultural and Rural Cooperation, 2018)
In the Solomon Islands, when one of Guadalcanal’s lead farmers lost his farm to flooding in 2014, a number of NGOs began supporting his farm’s rehabilitation. John Maeli planted new seedlings and started implementing climate-smart agriculture practices. Soon the rebuilding process had transformed his farm into a demonstration area and training hub for other farmers concerned about climate change and eager to learn more resilient practices.